2021
DOI: 10.1245/s10434-021-11045-3
|View full text |Cite|
|
Sign up to set email alerts
|

Microsatellite and RAS/RAF Mutational Status as Prognostic Factors in Colorectal Peritoneal Metastases Treated with Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy (HIPEC)

Abstract: Background. Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC) leads to prolonged survival for selected patients with colorectal (CRC) peritoneal metastases (PM). This study aimed to analyze the prognostic role of micro-satellite (MS) status and RAS/RAF mutations for patients treated with CRS. Methods. Data were collected from 13 Italian centers with PM expertise within a collaborative group of the Italian Society of Surgical Oncology. Clinical and pathologic variables and KRAS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…After the PRODIGE 7 study, there is a substantial consensus to consider cytoreductive surgery as surgery for CRC liver or lung metastases if adopted in the context of a multimodality approach to systemic chemotherapy after a multidisciplinary discussion of every single case [13,14]. Preoperative staging should be directed toward select patients with limited disease, and the indication for surgery should be balanced with other well-established prognostic factors such as primary tumor presentation (obstruction/perforation), signet ring histology, BRAF and MSI status, and the presence of liver metastases [15][16][17][18][19]. Another important result that should be underlined is the significant effect on the survival of HIPEC in patients with PCI between 11 and 15, although considering the whole population with PCI < 15, this result is not confirmed.…”
Section: Strengthsmentioning
confidence: 99%
“…After the PRODIGE 7 study, there is a substantial consensus to consider cytoreductive surgery as surgery for CRC liver or lung metastases if adopted in the context of a multimodality approach to systemic chemotherapy after a multidisciplinary discussion of every single case [13,14]. Preoperative staging should be directed toward select patients with limited disease, and the indication for surgery should be balanced with other well-established prognostic factors such as primary tumor presentation (obstruction/perforation), signet ring histology, BRAF and MSI status, and the presence of liver metastases [15][16][17][18][19]. Another important result that should be underlined is the significant effect on the survival of HIPEC in patients with PCI between 11 and 15, although considering the whole population with PCI < 15, this result is not confirmed.…”
Section: Strengthsmentioning
confidence: 99%
“… Frequency of histological (Kerscher et al , 2013; Hugen et al , 2014; Koemans et al , 2020), genomic (Schneider et al , 2018; Graf et al , 2020; Stein et al , 2020; Wang et al , 2020; Baratti et al , 2021; Breuer et al , 2021; Di Giorgio et al , 2021; Diez‐Alonso et al , 2021; Flood et al , 2022; Lenos et al , 2022; Tonello et al , 2022) and transcriptomic (Cristescu et al , 2015; Narasimhan et al , 2020; Laoukili et al , 2022; Lenos et al , 2022) features in patients with PM from gastric cancer or colorectal cancer versus reference cohorts (Cancer Genome Atlas Research Network, 2014; Guinney et al , 2015). Size of the symbols reflects relative enrichment in PM.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of other known drivers of CRC such as TP53 , SMAD4 , and PIK3CA are occasionally reported for CRC PM in literature (Lund‐Andersen et al , 2021), but low patient numbers make interpretation of these results difficult. In patients undergoing CRS‐HIPEC, BRAF mutations are mostly reported to be a negative prognostic factor (Schneider et al , 2018; Graf et al , 2020; Baratti et al , 2021; Di Giorgio et al , 2021; Flood et al , 2022; Tonello et al , 2022), although other studies report no survival difference between patients with BRAF mutant and BRAF wild‐type tumors (Massalou et al , 2017; Larsen et al , 2022). RAS mutations were also associated with poor prognosis in some studies (Schneider et al , 2018; Arjona‐Sanchez et al , 2019; Diez‐Alonso et al , 2021), while no difference was reported by others (Graf et al , 2020; Baratti et al , 2021; Larsen et al , 2022; Tonello et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously identified factors include specific molecular patterns, unique gene signatures, primary tumor site, histologic subtypes, burden of disease, nodal status, completeness of cytoreduction, extent of prior surgery, performance status, ascites, comorbidities and perioperative complications. [1][2][3][4][5][6][7][8] While those previously mentioned factors have been thoroughly investigated, another poorly evaluated focus has been the extent of disease at specific organ sites.…”
Section: Introductionmentioning
confidence: 99%